Hey whipple, squeeze this : the classic guide to creating great advertising - Sullivan, Luke (John Wiley & Sons, Inc., 2022)
"Hey Whipple, Squeeze This, has helped generations of young creatives in advertising make their mark in the field. The lessons about writing and art direction contained in 5 previous editions of Whipple are still relevant. Creativity is still king. But students of the craft now need additional guidance to ply their craft in a digital-first world. This edition contains important new chapters and updates that explain how to create great advertising in any format, including viral video content for YouTube and TikTok, content-marketing, social media, digital campaigns, as well as traditional television, radio, print and outdoor ads"--